INTERNATIONALIZING IDENTITIES IN POST-SOVIET CONTEXTS: A QUALITATIVE STUDY OF FACULTY IN HIGHER EDUCATION IN KAZAKHSTAN - Tazabek, Sholpan (Graduate School of Education, 2022)
This qualitative study explores how faculty members in higher education understand and experience internationalization. Driven by the idea that understandings of internationalization of higher education are strongly connected with the specific sociocultural contexts in which they are understood and enacted, this study sought to explore the perspectives of Kazakhstan-based university educators whose professional experiences have been established within the medley of post-Soviet reforms. What makes Kazakhstan a peculiar case of inquiry is that it represents a postcolonial context where nation-building rhetoric has been escalating along with the country’s aspirations for global and international education. At the same time, there are social and educational legacies of the Soviet Union that continue to remain strong in Kazakhstan, impacting the ways in which faculty members navigate within this controversy of trajectories in the country. Approached via in-depth interviews at two universities, this study analyzed faculty members’ perceptions and experiences through Gee’s (2000) perspective of identity. It emerged that internationalization of higher education represents a discursive space whereby faculty members experience a multiplicity of discourses and whereby they (re)construct their personal and professional identities. The study revealed how certain discourses of internationalization can determine certain ways of professional and personal positioning that faculty members knowingly or unknowingly take over. Concurrently, the findings indicated that while faculty members interpret internationalization in their individual ways, they may use their interpretations to negotiate their personal and professional identities in response to these discourses. This is explicit in post-Soviet contexts where historically developed definitions of academic professionalism may differ from hegemonic interpretations of internationalization, increasingly defining it as the synonym of academic excellence and academic success. Some discourses like, for instance, a “Scopus-driven internationalization” – a term that emerged in the findings of this study – may even lead to ill-conditioned and disruptive understandings of internationalization, resulting at best in academic homogeneity, and at worst in the loss of local academic traditions. The study raises these questions in light of a growing scholarly appeal to develop internationalization as a meaningful, inclusive, and a more ethical notion.
Keywords: Type of access: Restricted; post-Soviet context; discourse; identity; internationalization; higher education; faculty; Kazakhstan